A MULTI-DIMENSIONAL APPROACH TO IMPOSE UNIVERSAL JURISDICTION IN INTERNATIONAL LEGAL PRACTICE - Abdalla Abdelkarim, Yassin (International Journal of Law in Changing World, 2024)
The study introduces a multidimensional solution to impose universal jurisdiction by utilizing firm concepts in international law to enhance the functionality of this principle in international legal practice. Initially, it explores the current ‎classification of the principle of universal jurisdiction in international law to ‎determine its latest status quo. It is prominent to introduce a comprehensive presentation of the ‎structure of universal jurisdiction and its relevant concepts in international ‎law by ‎reviewing international jurisprudence on this principle. Thus, the study reviews its evolution in international legal instruments and how ‎international courts utilise them. In addition, the research analyzes the UN ‎relevant resolutions on universal jurisdiction to draw a global portrait of its ‎legal status in international law.‎ Because of the cosmopolitan humanitarian ends of universal jurisdiction, the research suggests employing the concept of humanness to justify imposing it. In addition, these ends, and the purpose of enhancing international justice, drive the study to introduce the theory of the responsibility to protect (R2P) to justify the utilization of domestic legal rules extra-territorially. Nevertheless, this utilisation might trigger the question of national judiciaries’ independence. The research analyzes this problem to establish the required foundations to strike a balance between the independence of national judiciaries and imposing universal jurisdiction to secure justice. _________ El estudio presenta una solución multidimensional para imponer la jurisdicción universal mediante la utilización de conceptos firmes en el derecho internacional para mejorar la funcionalidad de este principio en la práctica jurídica internacional. Inicialmente, explora la clasificación actual del principio de jurisdicción universal en el derecho internacional para determinar su status quo más reciente. Es importante introducir una presentación integral de la estructura de la jurisdicción universal y sus conceptos relevantes en el derecho internacional mediante la revisión de la jurisprudencia internacional sobre este principio. Así, el estudio revisa su evolución en los instrumentos jurídicos internacionales y cómo los tribunales internacionales los utilizan. Además, la investigación analiza las resoluciones relevantes de la ONU sobre jurisdicción universal para dibujar un retrato global de su estatus legal en el derecho internacional.‎ Debido a los fines humanitarios cosmopolitas de la jurisdicción universal, la investigación sugiere emplear el concepto de humanidad para justificar su imposición. Además, estos fines, y el propósito de mejorar la justicia internacional, impulsan el estudio a introducir la teoría de la responsabilidad de proteger (R2P) para justificar la utilización de normas jurídicas internas extraterritorialmente. Sin embargo, esta utilización podría plantear la cuestión de la independencia de los poderes judiciales nacionales. La investigación analiza este problema para establecer las bases necesarias para lograr un equilibrio entre la independencia de los poderes judiciales nacionales y la imposición de la jurisdicción universal para garantizar la justicia. ___________ 本研究提出了一种多维解决方案，即利用国际法中的明确概念来实施普遍管辖权，以提高这一原则在国际法律实践中的功能性。首先，它探讨了国际法中普遍管辖权原则的现行分类，以确定其最新现状。通过回顾有关这一原则的国际判例，全面介绍普遍管辖权的结构及其在国际法中的相关概念，这一点非常重要。因此，本研究回顾了普遍管辖权在国际法律文书中的演变，以及国际法院如何利用它们。此外，本论文还分析了联合国关于普遍管辖权的有关决议，以描述其在国际法中的法律地位。由于普遍管辖权具有世界性的人道主义目的，本研究建议采用人性概念来证明实施普遍管辖权的合理性。此外，这些目的以及加强国际正义的理想促使本研究引入保护责任（R2P）理论，以证明在域外适用国内法律规则的正当性。然而，这种适用可能会引发国家司法机构独立性的问题。本文分析了这个问题，为在国家司法机构独立性和实施普遍管辖权之间取得平衡奠定了必要的基础，以保障正义。